The optic syrinx: cavernous degeneration of the optic nerve demonstrated by iopamidol optic neurography. - Jinkins, J R (American Journal of Neuroradiology, 1987)
Cavernous degeneration of the optic nerve has been described predominantly in association with long-standing glaucoma, although less frequently it has been reported in other, disparate disease processes. The only descriptions to date have been in pathologic specimens in vitro. This is the first report to describe syrinx formation of the optic nerves in vivo in two patients with nonglaucomatous conditions affecting the optic nerves.